The impact of mobile health interventions on patients with schizophrenia: a meta-analysis - Ye, Yongli; Zhang, Fangrui; Zhou, Yangyang (Frontiers in Psychiatry, 2026)
ObjectiveTo systematically evaluate the impact of mobile health (mHealth) interventions on patients with schizophrenia.MethodsRandomized controlled trials (RCTs) concerning the effects of mHealth interventions on patients with schizophrenia were retrieved from databases including CNKI, WanFang, VIP, CBM, PubMed, Cochrane Library, Embase, and Web of Science from their inception until September 2025. Data analysis was performed using RevMan 5.4 software.ResultsA total of 10 RCTs involving 1135 patients with schizophrenia were included. The analysis results showed that the intervention group was significantly better than the control group in improving positive symptoms of schizophrenia (SMD = -0.18, 95% CI = -0.34 to -0.02, P = 0.03). The control group had a lower incidence of adverse events compared to the intervention group (OR = 2.30, 95% CI = 1.31 to 4.04, P = 0.004). There was no significant difference between the two groups in depressive symptoms (SMD = -0.02, 95% CI = -0.23 to 0.19, P = 0.83).ConclusionmHealth interventions demonstrate a slight but definite positive effect on improving positive symptoms in schizophrenia. However, they show no significant effect on improving depressive symptoms. While a higher incidence of adverse events was reported in the intervention group, this finding should be interpreted with caution as it may be influenced by enhanced detection through digital monitoring (surveillance bias).